Pediatric suicide by violent means: a cry for help and a call for action - Christina M. Theodorou; Kaeli J. Yamashiro; Sarah C. Stokes; Edgardo S. Salcedo; Shinjiro Hirose; Alana L. Beres (BMC, 2022)
Abstract Background Suicide is the second most common cause of death among adolescents and young adults. In the pediatric population, gunshot wounds (GSWs) and hangings are common mechanisms of pediatric suicide. Comorbid psychiatric illness is prevalent in this population, but psychiatric resource utilization after self-inflicted traumatic injury is not well characterized. Methods We analyzed patients < 18 years old presenting to a level 1 pediatric trauma center after suicide attempt by GSW, hanging, or jumping from a height from 2009 to 2019. The primary outcome was psychiatric resource utilization. Secondary outcomes included prior emergency department (ED) visits to identify prior opportunities for intervention. Results Of 6538 pediatric trauma patients, there were 219 GSWs, 7 hangings, and 7 jumps from height, for a total of 233 patients. Of these, 14 presented following a suicide attempt (four GSWs, six hangings, and four jumps, total 6.0%). Half of these patients died due to their injuries. Self-inflicted GSWs had the highest mortality (75%). Most surviving patients were placed on involuntary psychiatric holds (n = 5/7, 71.4%), and three patients were discharged to an inpatient psychiatric hospital (n = 3/7, 42.9%). Five of the 14 patients had prior ED visits (35.7%), and of these, 60% were for suicidal ideation or suicide attempts. Conclusions Among pediatric trauma patients, suicide attempts are rare, but are highly lethal, with the highest mortality rate seen in self-inflicted GSWs. Psychiatric resource utilization is high both during and after the hospitalization. Prior ED visits may represent opportunities for depression and suicidality screening in this at-risk population.